Taking cover before the outbreak: understanding precautionary behaviours of Chinese in Italy in the COVID-19 scenario - Proserpio, Licia; Cappi, Valentina; Albana, Alessandro (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
This paper provides an empirical exploration of the preemptive measures adopted by Chinese in Italy vis-à-vis the early outbreak of COVID-19. Based on a quantitative dataset obtained through an online survey, the assessment of preemptive self-isolation has been pursued in relation to: the sources of information regarding the pandemic, the perception of risk, the level of trust towards both Italian and Chinese authorities, and the level of perceived stigma. According to the evidences we have collected, most of the Chinese living in Italy began an “all-out self-isolation” prior to the enforcement of the national lockdown. Such behaviours appear as the result of individual decisions taken on the basis of an individual, high perception of risk, apprised by Chinese sources of information and fueled by distrust towards policies enforced by the Italian governmental authorities. This article suggests that the precautionary behaviours of the Chinese in Italy can be seen as the result of the combination of their “preparedness” and their perception of stigma and discrimination.